(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: In compliance with guidelines from NACP III, wide spread activities are continued, by public, private and NGO sectors, to enhance the level of knowledge about HIV/AIDS among vulnerable adolescent and young adult population in urban areas, in the forms of various projects, so as to facilitate positive behavioural changes among them . Present cross-sectional study, was conducted in three, representative administrative wards (namely L, K/East & R/North) of Municipal Corporation of Greater Mumbai (MCGM), India, in December 2010, to assess the level of knowledge and attitudes about HIV/ AIDS amongst the adolescents and young adults. Methodology: Total 4306, adolescents and young adults representing all 28 health posts from selected wards were interviewed by 100 trained NSS volunteers of University of Mumbai, under the leadership of Department of Community Medicine, T. N. Medical College & Nair Hospital. Data was analysed with the help of statistical software (SPSS). Results: Seventy-nine percent (3407/4306) and 49.81% (2145/4306), of respondents had heard about HIV/AIDS, and STI/RTIs respectively. Unsafe sexual relationship, as route of transmission is known to 51.81 % (2231/4306) respondents, whereas use of condom, as preventive measure is known to 87% (3746) of people. Only 30.05% (1294/4306) respondents know nearby testing facilities. Everybody should be tested for HIV, to reduce transmission, is believed by 93.96%, (4046/4306) respondents. Knowledge grade given to each respondent based on the score obtained by them out of total obtainable 25 score, reveals, 57.36%, (2470/4306), in poor grade. Multinomial logistic regression confi rms the signifi cant infl uence of age and education status of respondents on their knowledge and positive attitudes.] Conclusion: When compared with other relevant studies, the present status of knowledge of adolescents and young adults from slums of Mumbai appears to be poor and justifi es the need for intensifi ed efforts towards improving the same, taking into account their vulnerability. Well planned coordinated efforts of public, private and NGO sectors, would go a long way to get the desired impact. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS 2012; IX (1) 26-34 DOI: http://dx.doi.org/10.3126/saarctb.v9i1.6962